2010
DOI: 10.1111/j.1365-294x.2010.04665.x
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive success and its behavioural correlates in a polygynous mammal, the Galápagos sea lion (Zalophus wollebaeki)

Abstract: Sexual selection theory predicts competitive males and choosy females. Nevertheless, since molecular marker-based studies, paternity outside the expected mating patterns has increasingly been described. Even in highly polygynous systems, where paternity is expected to be strongly skewed towards large, dominant males, alternative mating tactics have been suggested. We examined reproductive success in the polygynous Galápagos sea lion (Zalophus wollebaeki). Semiaquatic territoriality allows females to move freel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 64 publications
3
38
0
Order By: Relevance
“…In previous work, we have shown that male behaviour influences paternity success [33]. From the individuals investigated in 2006 and 2007, we here took a subset for which we now had obtained MHC-DRB genotypes (100/146) and rerun their best model (table 3 in [33]).…”
Section: (D) Genotypic Effects Of Mhc and Inbreeding On Fitnessmentioning
confidence: 99%
“…In previous work, we have shown that male behaviour influences paternity success [33]. From the individuals investigated in 2006 and 2007, we here took a subset for which we now had obtained MHC-DRB genotypes (100/146) and rerun their best model (table 3 in [33]).…”
Section: (D) Genotypic Effects Of Mhc and Inbreeding On Fitnessmentioning
confidence: 99%
“…We conducted 2 to 3 daily resight rounds (between 05:00 and 18:00 h), noting the presence of each male identified from numbered tags, permanent characteristics or bleach marks. In total, we observed 227 individually identified adult males (≥5 yr old; Pörschmann et al 2010). In addition to the ID of a focal male, we recorded the ID of its closest associates.…”
Section: Methodsmentioning
confidence: 99%
“…In polygynous species, male reproductive success is expected to increase with male body size and mass ([5],[6]) which have been selected for increased fasting ability ([2],[7]) or advantages in intra-sexual competition for access to females ([8],[9]). Furthermore, body length and mass have been used as indicators to assess habitat quality (e.g., [10]) as an individual’s body condition provides information about the quantity and quality of resources in a habitat (e.g., [11], [12]).…”
Section: Introductionmentioning
confidence: 99%